Leaders in the Expansive and Restrictive Interpretation of Investment Treaties: A Descriptive Study of ISDS Awards to 2010. (23rd July 2018) - Van Harten, Gus
Abstract: This article provides an empirical analysis of interpretive discretion in investor–state dispute settlement (ISDS). Since the late 1990s, foreign investors have brought hundreds of investment treaty claims against states, leading to numerous awards in which arbitrators have interpreted investment treaties. Arbitrators may resolve ambiguities in the treaties in expansive or restrictive ways, thereby affecting the compensatory promise of ISDS for foreign investors and corresponding risks for states. Which arbitrators have contributed most to expansive or restrictive approaches? To examine this question, data was analysed on arbitrators' resolutions of contested legal issues, such as the permissibility of parallel or minority shareholder claims and the scope of concepts of investment, fair and equitable treatment, full protection and security and indirect expropriation. The analysis allows for rankings of arbitrators and tentative descriptive findings identifying a small group of individuals as the leading contributors to expansive resolutions and one individual as the leading contributor to restrictive resolutions. The analysis reveals how interpretive discretion impacted relevant legal aspects of ISDS in its first two decades and supplements other research on ISDS arbitrator behaviour.